Penerapan Analisis Regresi Spatial Durbin Model Terhadap Penyakit Tuberkulosis Di Provinsi Sulawesi Selatan Tahun 2022 - Hadi, Muhammad Akhyar; Aswi; Mar'ah, Zakiyah (Program Studi Statistika Fakultas MIPA UNM, 2025)
By supplying geographical effects at several sites that serve as the centre of observation, the spatial regression analysis approach assesses the connection between a single variable and multiple other variables. The Spatial Durbin Model is one technique utilised in spatial regression analysis. A special instance of the spatial autoregressive model (SAR) is the spatial Durbin model, which incorporates a spatial lag into the model by adding a lag influence to the independent variables. The goal of this study is to develop a Spatial Durbin model and identify the variables that significantly affect tuberculosis (TBC) in the province of South Sulawesi. The results of this research obtained a Spatial Durbin Model regression model which was significant at a significant level of P-value <α=0.1) using variable influencing factors with a determination coefficient (R2) of 49.74%. Elements that possess a noteworthy impact on the number of Tuberculosis (TB) diseases in South Sulawesi Province are per capita income.